(untitled) (Human Factors in Design, 2025)
This article aims to present a digital interface in Augmented Reality in an IoT (Internet of Things) system and its usability analysis based on user tests. To carry out this research, the Double Diamond method was applied to understand the requirements of personas and promote innovation in the construction of the interface for the industrial sector. The results confirm that the developed interface: (1) has easy user adaptation to manipulate virtual elements inserted in the physical world; (2) it promotes more agility and efficiency in the management, training and mentoring process. In this way, it is considered appropriate for implementation in a factory.